The Multi-Resolution Migration Imaging Method for Grounded Electrical Source Transient Electromagnetic Virtual Wavefield - Kailiang Lu; Xiu Li; Jianhua Yue; Ya’nan Fan; Qinrun Yang; Xiaozhen Teng (Applied Sciences)
The traditional source uses a square wave with a fixed fundamental frequency to excite transient electromagnetic (TEM) fields, with harmonic energy primarily concentrated in the low-frequency range, limiting the detection resolution of the TEM. The differential pulse, composed of two square waves with identical pulse widths but opposite polarities, concentrates harmonic energy more effectively. By adjusting the pulse width of the differential pulse, the concentration frequency band of harmonic energy can be changed, enabling multi-resolution detection of geological structures at different depths. In this study, TEM fields are excited using differential pulses of varying pulse widths during power supply. A preconditioned precise integration time-sweeping wavefield reverse transformation method is applied to interpret the virtual wavefield from the diffusion field, effectively improving the numerical accuracy and noise resistance of the virtual wavefield. Then, the finite-difference migration imaging method is used to obtain imaging profiles for differential pulses of different pulse widths, and stacking techniques are applied to acquire high-resolution characteristics of electrical interfaces at various depths. Finally, the feasibility of the method is verified through a complex geological model. By comparing the relative anomalies of square waves and differential pulses with different pulse widths, the results show that the electromagnetic anomalies for differential pulses are increased by 53.7%. Therefore, using differential pulses as the excitation source leads to higher-resolution electromagnetic responses, which in turn result in high-resolution imaging.